Estudo da correlação entre largura da zona de estiramento e energia de impacto para o aço 4340 sujeito a ciclos de transformação martensítica - Dorta, Natalia de Cerqueira [UNESP] (2016)
Stretch zone is a switch-over zone on fractures surface, between the end of stable crack propagation and the beginning of unstable propagation (final rupture). This zone straining can be related to the released energy during the material failure. Nowadays, the morphological evaluation of stretch zone is performed through SEM images, a time-consuming and costly technique. Moreover, it is an inaccurate analysis, since the measurements are made on the projection of the relief, and not in an effectively three-dimensional context. In this study, an alternative methodology for the morphological evaluation of the stretch zone was developed using confocal microscopy and its tools and programs of superficial analysis, a faster and lower-cost analysis. Furthermore, it's wanted to evaluate combined use feasibility of stretch zone height and width, computing the hypotenuse of the triangle formed with these two parameters as hinges, in correlation with the impact energy, leveraging the three-dimensional context of measurements performed in a confocal optical profilometer